Growth of Pak Coy Varieties (Brassica rapa L. ssp. chinensis (L.)) with Applied NAA (Naphthalene-3-acetic Acid) on Floating Hydroponics Medium - Ari Fradana Nst; Revandy Iskandar M. Damanik; Eva Sartini Bayu (Jurnal Agroekoteknologi, 2018)
The objective of the research was to know growth respons of Pak Coy varieties with applied NAA on floating hydroponics medium. This research was conducted at experimental fields on Compost Centre, Faculty of Agriculture, University of Sumatera Utara, from February-April 2017 with factor such as varieties (Green and Red) and applied NAA (0, 10, 20 ppm) using two way randomized design then analyzed using Duncan Multiple Range Test on 5%. The parameters observed were plants length, number of leaf, chlrorophyll values, stems diameters, roots length, fresh weight per sample,fresh weight per plot and fresh apical weight. The results showed that varieties was significantly different on number of leaf 3, 4, and 5 weeks after planted, chlrorophyll values on morning, noon and afternoon, stems diameters, fresh weight per sample,fresh weight per plot and fresh apical weight. Applied NAA on hydroponics medium was significantly different on all parameters. Keywords: hydroponics, naphthalene-3-acetic acid, pak coy, varieties